Who Really Cares : the Surprising Truth About Compassionate Conservatism -- America's Charity Divide--Who Gives, Who Do. - Brooks, Arthur C. (Basic Books, 2007)
Surprising proof that conservatives really are more compassionate--and more generous--than liberals.